Advertising creative : strategy, copy, and design - Altstiel, Tom (Los Angeles : SAGE, 2023)
"Advertising Creative, Sixth Edition gets right to the point of advertising by stressing key principles and practical information students and working professionals can use. Drawing on personal experience as award-winning experts in creative advertising, this new edition offers real-world insights on cutting-edge topics, including global, social media, business-to-business, in-house, and small agency advertising. In the new edition, the authors take a deeper dive into the exploration of digital technology and its implications for the industry, as they expose the pervasive changes experienced across the global advertising landscape. Their most important revelation of all is the identification of the three qualities that will define the future leaders of this industry: Be a risk taker. Understand technology. Live for ideas. The latest edition addresses some of the key issues impacting our industry today, such as diversity in the workplace, international advertising, and expanded coverage of design in the digital age. "--
Includes bibliographical references and index.
Keywords: Advertising